Annual growth rings thickness and trees total volume calculation of Acacia melanoxylon - Rucha, Andreia (2007)
This text presents some results on the variation of Blackwood (Acacia melanoxylon R. Br.) annual growth rings thickness in Portugal, as well as the best models to evaluate total volumes stand trees, under or over-bark. Annual ring thickness evaluations were done on 261 wood sample disks collected at the usually used levels. With the purpose of obtaining those disks, 20 sample trees of 40cm dbh were harvested in four northwest sites of Portugal. The study of earlywood and latewood thickness leads to the conclusion that the wood type is responsible for 16% of ring size variance, and earlywood is 61% larger in average than latewood. The site, number of ring and its interaction are responsible for 12% of annual woody increment variation. Respective residuals are very relevant in both cases - 75 and 88%. Based on the study of those wood variables, the four places were arranged into three independent homogeneous groups. Differences between averages of earlywood and latewood thickness were significative, as well as those between North and South exposures. The selected model (v=β1*dβ2*hβ3) that uses sites as dummy variables for stand tree volumes estimation is also presented. Maximum expected errors perform values between 155dm3 to mean maximum volumes of 1362dm3 under-bark, and 169dm3 to mean maximum volumes of 1459dm3 over-bark.